From the Tatami Mat to the Printed Page: Author Barry Eisler Keeps His Fiction Real - Brian R. Sheridan (Universidad de León, 2012)
This article looks at how a lifelong passion for the martial arts has influenced the writing of international bestselling thriller author Barry Eisler. His seven novels have garnered for him a reputation for authenticity, from his approach to fight scenes to the use of modern espionage techniques. Eisler discusses how he trained at the Kodokan, the birthplace of modern judo in Japan, and its impact on his anti-hero protagonist, John Rain. He also talks about the reaction martial artists have had toward his work. 2009 looks to be a major year for Eisler as his first non-Rain book hits bookstores and a movie based on his first novel is released.